2016
DOI: 10.1111/jce.13089
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Implantable Cardiac Monitor to Detect Atrial Fibrillation: Results of the DETECT AF Study

Abstract: The SJM Confirm DM2102 can accurately and repeatedly detect paroxysmal AF episodes of at least 2 minutes in length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 17 publications
0
43
0
2
Order By: Relevance
“…For example, in the Reveal XT Performance Trial (XPECT), the detection algorithm of the Reveal XT ICM (Medtronic, Minneapolis, MN, USA) identified AF patients with a sensitivity of 96.1% and specificity of 85.4% (R‐R interval variation analysis), compared with 100% sensitivity and 88.1% specificity for the patient‐based approach in our study. For the St. Jude Medical Confirm TM device (St. Jude Medical, St. Paul, MN, USA), 100% sensitivity and 85.7% specificity have been reported in a similar approach . The successor device to Reveal XT, Reveal LINQ, using both R‐R interval variation and a new P‐wave recognition algorithm for AF detection, demonstrated an improved sensitivity of 97.4% and specificity of 97.0% for patient‐based analysis of AF .…”
Section: Discussionmentioning
confidence: 95%
“…For example, in the Reveal XT Performance Trial (XPECT), the detection algorithm of the Reveal XT ICM (Medtronic, Minneapolis, MN, USA) identified AF patients with a sensitivity of 96.1% and specificity of 85.4% (R‐R interval variation analysis), compared with 100% sensitivity and 88.1% specificity for the patient‐based approach in our study. For the St. Jude Medical Confirm TM device (St. Jude Medical, St. Paul, MN, USA), 100% sensitivity and 85.7% specificity have been reported in a similar approach . The successor device to Reveal XT, Reveal LINQ, using both R‐R interval variation and a new P‐wave recognition algorithm for AF detection, demonstrated an improved sensitivity of 97.4% and specificity of 97.0% for patient‐based analysis of AF .…”
Section: Discussionmentioning
confidence: 95%
“…Several approved ILR devices are available (fig 7 and fig 8). 82 In general, most automated algorithms use variability in the R-R interval to detect atrial fibrillation 838485. Some newer devices’ algorithms also incorporate the presence/absence of a P wave 86Table 7.…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Some newer devices’ algorithms also incorporate the presence/absence of a P wave 86Table 7. summarizes studies evaluating the sensitivity and specificity of ILRs 83848587…”
Section: Newer Detection Methodsmentioning
confidence: 99%
“…Both studies, however, showed that more than half of all AF episodes recorded on the ILR were false positives episodes, which resulted in a low positive predictive value. The DETECT-AF study evaluated the performance of the St. Jude Medical Confirm DM2102 ILR using the 48-hour Holter recording as a criterion standard [24]. There were no instances where the patients had an AF episode that was recorded by the Holter but missed by the ILR.…”
Section: Discussionmentioning
confidence: 99%
“…The improved detection of AF occurrence and AF characterization compared to intermittent ECG monitoring could significantly impact the clinical treatment decisions [16]. However, many studies on AF detection using ILRs have shown a lower-than-expected positive predictive value (PPV) due to a higher rate of false positive episodes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%